RELATION OF ROLE PLAYING THERAPEUTIC TO TEENAGER TRUST ADOLESCENCE (Studies on Orphanage Foundation Assolihin-Candi-Mulyo-Jombang) - Riyandi Trisna Rukmana Hadi; Hindiyah Ike; Anita Rahmawati (Jurnal Keperawatan, 2012)
Adolescence are defined as the development of the transition between the children and adulthood includes biological change, social cognitive and emotional, and confidence adolescence. Orphanage adolescence tend to be more closed and less have confidence. The research analyst to know the therapeutic play a role playing against the of trust adolescence in Foundation an orphanage Assolihin-Candi-Mulyo-Jombang. The kind of research pra eksperiment, the population is all adolescence in Foundation an orphanage Assolihin-Candi-Mulyo-Jombang some 38 people, with the total sample 34 people with Non Probability Sampling with a kind of Purposive Sampling, independent variables the therapeutic play a role playing, dependent variables against the of trust adolescence. The collection of data using a questionnaire, using data available for analysis Wilcoxon. The research results show that most the levels of trust teens negative therapy before done playing as much as 22 people (64,7%), mainly the of trust teens positive therapy after done playing as much as 23 people (67,6%). The results of the analysis through test Wilcoxon while a mistake 0,05 and values p totaling 0,001, where p=0,001<0,05 then H1 accepted or H0 rejected it means there is a relationship the therapeutic play a role playing against the of trust adolescence in Foundation an orphanage Assolihin-Candi-Mulyo-Jombang.It is hoped that department of health can work together with the related units such as Health Center and Foundations in helping adolescence in improving confidence adolescence an orphanage.